Histopathological and radiographic characterization of the lesions of pododermatitis in sheep: support for the establishment of the foot injuries degree and its prognosis - Silveira, Caroline da Silva; Moreira de Morais, Raissa; Araújo Damboriarena, Pedro; Pozzobon, Ricardo; Fraga, Martín; Leite dos Anjos, Bruno (Frontiers in Veterinary Science, 2025)
Foot diseases in small ruminants cause locomotor disorders, leading to significant economic, productive, and health concerns in sheep and goat farming worldwide. The diagnosis and classification of lesions caused by footpad dermatitis are complex and based only on clinical observations in the field. In this context, this study assessed the histopathological and radiographic characteristics of lesions caused by pododermatitis in sheep to improve and deepen the classification of lesions and optimize diagnosis and prognosis. In this study 1.701 lame sheep were included and were distributed across 21 farms in southern Brazil. Lesions were categorized into three severity grades based on clinical, histological and radiographic observations. As a result of these findings, the lesions were categorized into 3 grades described as: mild interdigital dermatitis (grade 1), necrosis with bone involvement (grade 2) and severe tissue loss with osteolysis (grade 3). Radiographic evaluation revealed bone changes ranging from mild inflammation to osteomyelitis and pathological fractures in advanced grades. Histologically, in most severe cases, progressive inflammation, thrombosis and necrosis were observed. The results suggest that regardless of the origin of pododermatitis, whether related to environmental factors and/or agents such as Dichelobacter nodosus and Fusobacterium necrophorum, the lesions are progressive and severe. This adapted classification system can help field technicians and producers to effectively diagnose and treat these lesions depending on the grade, limiting their progression and consequently reducing economic losses. This integrated approach can improve animal welfare and productivity in South American herds, where these diseases are a significant concern.